Purificação de celulase produzido por Aspergillus niger utilizando sistema bifásico aquoso peg/citrato e aplicação em hidrólise de biomassa lignocelulósica - Varandas, Vinícius Silva (2020)
Cellulases are high value added enzymes in the market because they act in synergy to release sugars, of which glucose is the one that arouses the greatest industrial interest. However, the high cost of producing and purifying these enzymes is a limiting factor for the development of this technology. The objective of this study was to purify Aspergillus niger cellulase in a PEG/citrate aqueous biphasic system (SAB) for lignocellulosic biomass hydrolysis. The determination of the liquid-liquid equilibrium data of the PEG / Citrate systems showed that the methodologies employed were efficient in their characterization, where it was possible to verify that the tie-lines of the phase diagrams were practically parallel, obtaining average angular coefficients for each system. The purification of CMCase showed that it has a preference for the bottom phase (rich in salt), with a minimum partition coefficient of 0.31, purification factor of 7.73 and recovery yield of 90.69%. The operating conditions that led to this optimum were with PEG 6000, volume ratio of 0.25 and TLL of 32.3, the last two being the variables that most influenced statistically the enzyme partition. As with the other proteins, FPase showed a preference for the top phase (polymer rich), with the partition point of 2.69, recovery yield of 86.79% and purification factor of 2.80 as the optimal point in operating conditions with PEG 4000, volume ratio of 0.75 and TLL of 32.3. Leaf residues are viable for both enzyme production and sugar production. In the hydrolysis of this lignocellulosic biomass, the purified cellulase allowed a final concentration of 6.07 g/L of glucose in the reaction medium and a maximum productivity of 0.872 g/L.h against 4.89 g/L and 0.650 g/L.h obtained using the extract. which shows that cellulase purification in SABs is an important strategy in enzyme recovery without causing loss of catalytic activity.